AWARENESS OF FARMERS AND TRADERS TOWARDS BENEFITS OF ELECTRONIC NATIONAL AGRICULTURE MARKET (E-NAM) - NITISH KUMAR SINGH*; M. V. ALAGAWADI (The Journal of Research ANGRAU, 2023)
The study aims to comprehend the scope of e-platforms in the agriculture sector viz., e-NAM (e- National Agriculture Market), launched by the Government of India in 2016 and to solve the inherent problems andstudy aimed to explore the awareness of farmers and traders towards the e-NAM benefitsin three selected mandis (markets) in Andhra Pradesh. The sample constituted for the studycomprised of 110 farmers and 90 traders across Andhra Pradesh mandis selected through quota sampling method.Garrett’s ranking technique and the chi-square test areused to analyse data in SPSS software. The study revealed that educational qualification and age are essential factors in creating the awareness of e-NAM and surfaced thatthe benefits of the electronic platform would effectively reach the farmers and traders through strategies for sensitisation towards e-NAM.